Dental caries prevalence, prospects, and challenges for latin america and caribbean countries: a summary and final recommendations from a regional consensus (2021)
Dental caries can be effectively managed and prevented from developing into cavitated lesions while preserving tooth structure at all levels. However, the strong correlation between caries and socioeconomic factors may compromise the efficacy of preventive strategies. The high prevalence of persistent inequalities in dental caries in Latin American and Caribbean countries (LACC) is a matter of concern. The estimates of the burden of disease in some countries in this region are outdated or absent. This paper aims to summarize and present the final recommendations of a regional Consensus for Dental Caries Prevalence, Prospects, and Challenges for LACC. This consensus is based on four articles that were written by a team of Latin American experts, reviewed by dental associations, and presented and discussed in two consensus events. The following domains were explored: epidemiology, risk factors, prevention strategies, and management of dental caries with a focus on restorative procedures. Dental caries can manifest throughout the lifespan of an individual, making it a matter of concern for infants, children, adults, and older people alike. The prevalence rates of untreated caries in deciduous and permanent teeth are high in many parts of the world, including LACCs. Previous evidence suggests that the prevalence of dental caries in 12-year-olds is moderate to high in most Latin American countries. Moreover, the prevalence of treatment needs and dental caries in the adult and elderly population can also be regarded as high in this region. The risk/protective factors (e.g., sugar consumption, exposure to fluoride, and oral hygiene) probably operate similarly in all LACCs, although variations in the interplay of these factors in some countries and within the same country cannot be ruled out. Although salt and water fluoridation programs are implemented in many countries, there is a need for implementation of a surveillance policy. There is also room for improvement with regard to the introduction of minimal intervention techniques in practice and public health programs. Dental caries is a marker of social disadvantage, and oral health promotion programs and interventions aimed at reducing the burden of dental caries in LACCs must consider the complexity of the socioeconomic dynamics in this region. There is an urgent need to promote engagement of stakeholders, policymakers, medical personnel, universities, dental associations, community members, and industries to develop regional plans that enhance the oral health agenda for LACCs. A list of recommendations has been presented to underpin strategies aimed at reducing the prevalence and severity of dental caries and improving the quality of life of the impacted LACC population in the near future.